2019
DOI: 10.1186/s12887-019-1727-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the growth of infants diagnosed with cystic fibrosis by newborn screening

Abstract: Background Newborn screening (NBS) for cystic fibrosis (CF) improves nutritional outcomes. Despite early dietetic intervention some children fail to grow optimally. We report growth from birth to 2 years in a cohort of children diagnosed with CF by NBS and identify the variables that influence future growth. Methods One hundred forty-four children were diagnosed with CF by the West Midlands Regional NBS laboratory between November 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…These mean values are the same as in France, Germany, and Denmark, according to an ECFS report. 22 In a study by Patterson et al 23 the rate of malnutrition was mild in cases diagnosed at infancy. Neonatal screening for CF has been performed in Turkey since 2015.…”
Section: Discussionmentioning
confidence: 94%
“…These mean values are the same as in France, Germany, and Denmark, according to an ECFS report. 22 In a study by Patterson et al 23 the rate of malnutrition was mild in cases diagnosed at infancy. Neonatal screening for CF has been performed in Turkey since 2015.…”
Section: Discussionmentioning
confidence: 94%
“…In a prospective longitudinal multicenter study of 99 infant PWCF, Munck et al 24 found an association between WFA and LFA z scores and the presences of initial pulmonary symptoms as well as an association between LFA z score and hospitalization for respiratory symptoms and Staphylococcus aureus infection. In comparison, Patterson et al 25 found an association between a single isolation of Pseudomonas aeruginosa and reduced weight and height in infant PWCF in the first 2 years of life. Similarly, the Baby Observational and Nutrition Study (BONUS) found lower weight or length in the 1st year of life was associated with P. aeruginosa infection, MI, PI, male sex, and histamine blocker use 26 .…”
Section: Discussionmentioning
confidence: 93%
“…Our results suggest that there could be other factors which play a greater role in growth and nutrition outcomes during infancy and toddlerhood in PWCF besides sZn. Multiple studies have reported an association with growth in PWCF and exocrine pancreatic function 24,25 . In a prospective longitudinal multicenter study of 99 infant PWCF, Munck et al 24 found an association between WFA and LFA z scores and the presences of initial pulmonary symptoms as well as an association between LFA z score and hospitalization for respiratory symptoms and Staphylococcus aureus infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that even in developed countries, neonates screened positive for CF by newborn screening (NBS) develops growth retardation by the time diagnosis is confirmed by 3 weeks of age. [ 8 ] The challenge for a primary care physician in India is that there is neither NBS for CF in the country nor national guidelines to aid early identification of these infants. [ 9 ] Unless affected infants are diagnosed at the earliest, the therapeutic window for better nutrition is lost.…”
Section: Introductionmentioning
confidence: 99%